Cytokinin Oxidase (CKX) Family Members in ‘duli’ (Pyrus betulifolia Bunge): Genome-Wide Identification and Tissue Expression Profile Under Abiotic Stress - Weimin Wang; Ting Xie; Jiaojiao He; Kuozhen Nie; Zijuan He; Yuxing Zhang; Yingli Li (Horticulturae)
Cytokinin oxidases/dehydrogenases (CKXs) play a crucial role in modulating plant stress resistance by degrading cytokinins. The ‘duli’ pear (Pyrus betulifolia Bunge), a highly stress-resistant cultivar, is widely used as a rootstock in pear cultivation. This study aims to comprehensively identify and characterize the PbCKX gene family in ‘duli’. A total of 10 PbCKX genes were identified, which are unevenly distributed across five chromosomes and classified into four groups based on sequence similarity and phylogenetic relationships. The PbCKX genes exhibit a high degree of conservation in motifs and structural features, although exon structure variations are observed. Comparative analysis revealed 10 homologous gene pairs between ‘duli’ and Arabidopsis and 14 pairs between ‘duli’ and apple. Additionally, cis-acting elements related to abiotic stress, hormone responses, and light responsiveness were identified in the promoter regions of the PbCKX genes. RNA-seq analysis showed that PbCKX1 and PbCKX2 were predominantly expressed in roots, while PbCKX3 to PbCKX10 had higher expression in leaves. The PbCKX genes responded to both exogenous hormones and salt stress, with salt stress inducing a more pronounced response. Most abiotic stress treatments led to the downregulation of PbCKX4 and PbCKX9, while PbCKX6 and PbCKX8 were upregulated. Notably, treatments with Abscisic acid and NaCl significantly enhanced CKX enzyme activity in ‘duli’ over 20 days, reducing levels of zeatin and isopentenyladenine. Conversely, treatments with gibberellin, cytokinin, and auxin significantly reduced CKX enzyme activity and increased concentrations of zeatin and isopentenyladenine over the same period. These findings provide valuable insights for future studies on the functional role of PbCKX genes in abiotic stress responses in ‘duli’.